2021
DOI: 10.1016/j.cegh.2021.100833
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with women's exposure to mass media for Health Care Information in Ethiopia. A case-control study

Abstract: Introduction: Mass media are often essential to communicate health messages. Women's exposure to mass media remained low in Ethiopia. Evidence was scarce on underlined factors for enhancing women's exposure to mass media.Objective: This study aimed to assess factors associated with women's exposure to mass media in Ethiopia. Methods:The study was a secondary data analysis of the Ethiopian demographic and health survey 2016. A casecontrol study applied with frequency matching by place of residence and women's e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Therefore, pregnant women from households with better economic status can pay direct health service costs like transportation costs and indirect costs like household and work obligations, while mothers from poorest households need financial capacity to support their daily living and therefore, they may be spent more time on economic activities to cater to their families rather than their health. Besides, mothers from wealthy families have access to information about maternal healthcare through mass media [ 44 ]. In contrast study conducted in Nigeria shows that mothers from poorer households had 52% lower odds of use ANC compared to mothers from poorest household [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pregnant women from households with better economic status can pay direct health service costs like transportation costs and indirect costs like household and work obligations, while mothers from poorest households need financial capacity to support their daily living and therefore, they may be spent more time on economic activities to cater to their families rather than their health. Besides, mothers from wealthy families have access to information about maternal healthcare through mass media [ 44 ]. In contrast study conducted in Nigeria shows that mothers from poorer households had 52% lower odds of use ANC compared to mothers from poorest household [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 34 This might be related to less frequent mass-media exposure of females, the cultural taboo, and females being given few opportunities and fewer options. 41 The other reason is that women are more likely to have physiological circumstances that prevent them from donating blood like menstruation and bleeding during pregnancy and delivery. 42 This suggests that women should be informed more about the health advantages of blood donation and health information delivery through campaigns and different sources of information.…”
Section: Discussionmentioning
confidence: 99%
“…One intervention study found that utilizing a cell phone increased antenatal care service usage by a considerable proportion and that women were increasingly accessing preventive health services [ 31 ]. Further, owning a mobile phone is associated with a favorable attitude regarding the use of mobile technology for maternal health services [ 32 ] and can facilitate exposure to mass media [ 15 ]. Having a mobile phone boosts possible access to health information, engagement with health practitioners, and quality health services.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, employing a mobile phone as a tool for interpersonal communication is an essential component of healthcare communication because its applications are expanding over time, and the digitalization effect should reach the limits as time passes. Additionally, women’s exposure to mass media is aided by their availability to mobile phones and constant connectivity with health practitioners [ 15 ]. Mobile technology, as a faster mode of communication, has the potential to significantly improve access to emergency obstetric care (EmOC), which includes care necessary during and immediately following delivery [ 16 ].…”
Section: Introductionmentioning
confidence: 99%